Reseña del libro Latin America, China, and Great Power Competition: New Triangular Relations - Kim, Won-Ho (México y la Cuenca del Pacífico, 2026)
Dussel Peters, E. (2025). Latin America, China, and Great Power Competition: New Triangular Relations. Lynne Rienner Publishers, Inc., 193 pp.